2021
DOI: 10.1002/cpdd.962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silymarin Treatment on Circulating Bilirubin and Cardiovascular Disease Risk Factors in Healthy Men: A Single‐Blind, Randomized Crossover Trial

Abstract: This clinical trial (ACTRN12619001296123) investigated the impact of silymarin (Legalon®) on circulating bilirubin concentration, lipid status, systemic inflammation, and antioxidant status. The study design was a randomized, placebo‐controlled, single‐blind crossover trial of healthy men (18‐65 years), conducted at Griffith University, Gold Coast, Australia. Participants were recruited from Griffith University and were randomized to silymarin (140 mg silymarin capsules thrice daily) or placebo (3 capsules con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…(c) Inhibitory effects on adipogenesis factors, such as CCAAT enhancer-binding protein α (C/EBPα), peroxisome proliferatoractivated receptor γ (PPARγ) and fatty acid-binding protein 4 (FABP4) that could decrease lipid accumulation and normalize serum lipids (Ji, 2017;Suh, Cho, Kim, & Choi, 2015); (d) reducing liver synthesis of cholesterol and biliary cholesterol concentrations by Silybin (one of silymarin constituents) (Vidimce et al, 2021); (e) inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase as a main enzyme of cholesterol synthesis in dose-dependent manner (Federico, Dallio, & Loguercio, 2017;Mahdavi, Bagherniya, & Fakheran, 2020). (c) reducing advanced glycation end products (AGEs) formation (Wu, Huang, & Yen, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Inhibitory effects on adipogenesis factors, such as CCAAT enhancer-binding protein α (C/EBPα), peroxisome proliferatoractivated receptor γ (PPARγ) and fatty acid-binding protein 4 (FABP4) that could decrease lipid accumulation and normalize serum lipids (Ji, 2017;Suh, Cho, Kim, & Choi, 2015); (d) reducing liver synthesis of cholesterol and biliary cholesterol concentrations by Silybin (one of silymarin constituents) (Vidimce et al, 2021); (e) inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase as a main enzyme of cholesterol synthesis in dose-dependent manner (Federico, Dallio, & Loguercio, 2017;Mahdavi, Bagherniya, & Fakheran, 2020). (c) reducing advanced glycation end products (AGEs) formation (Wu, Huang, & Yen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of silymarin on blood lipids can be partly explained by the following potential mechanisms: (a) Prohibition of intestine cholesterol absorption with prohibition of acyl‐CoA like cholesterol acyltransferase as a main pathway of lipid metabolism (Orolin et al, 2007; Sobolová, Škottová, Večeřa, & Urbánek, 2006; Tajmohammadi, Razavi, & Hosseinzadeh, 2018); (b) Activating beta‐oxidation of fatty acids in mitochondria (Škottová et al, 2004); (c) Inhibitory effects on adipogenesis factors, such as CCAAT enhancer‐binding protein α (C/EBPα), peroxisome proliferator‐activated receptor γ (PPARγ) and fatty acid‐binding protein 4 (FABP4) that could decrease lipid accumulation and normalize serum lipids (Ji, 2017; Suh, Cho, Kim, & Choi, 2015); (d) reducing liver synthesis of cholesterol and biliary cholesterol concentrations by Silybin (one of silymarin constituents) (Vidimce et al, 2021); (e) inhibiting 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase as a main enzyme of cholesterol synthesis in dose‐dependent manner (Federico, Dallio, & Loguercio, 2017; Mahdavi, Bagherniya, & Fakheran, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this reduction in bilirubin levels is in contrast with previous clinical studies, which reported inconsistent effects of silymarin treatment on serum bilirubin levels, with some studies reporting no effects and others reporting increased bilirubin concentrations. 9 In this case report, reduction in serum bilirubin levels following silymarin treatment may be linked to its anti-inflammatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 77%
“…Medical applications of milk thistle have been thoroughly demonstrated by many experiments for more than 50 years [5][6][7][8]12,[14][15][16]19,20,116,[130][131][132][133][134][135], and interest in silymarin has increased in the fields of medical, pharmaceutical, and veterinary sciences due to its wide use in various therapies and medical applications [18,101,136,137]. However, the yield potential and the chemical composition of milk thistle fruits and vegetative biomass have suggested a variety of additional uses, ranging from livestock feeding to human consumption and industrial exploitation, and involving several plant parts, derivatives, and extracts (Tables 1-3).…”
Section: Utilizationsmentioning
confidence: 99%